2011
DOI: 10.3945/ajcn.110.005413
|View full text |Cite
|
Sign up to set email alerts
|

Plasma choline depletion is associated with decreased peripheral blood leukocyte acetylcholine in children with cystic fibrosis

Abstract: A low free choline and methyl status in children with CF is associated with reduced acetylcholine in leukocytes. Whether these changes are explained by a mutation in the CF transmembrane conductance regulator or disturbances in choline metabolism and the implications for immune cell dysfunction in CF are unknown. This trial was registered at clinicaltrials.gov as NCT01150136.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
(49 reference statements)
3
15
0
Order By: Relevance
“…Our lack of association may also be attributed to the high plasma choline concentration (status) of the children in the Seychelles. A previous study only observed a relationship between plasma choline concentration and leucocyte ACh concentration in children who had low choline status (45) ; no relationship was evident in children who had plasma concentrations of choline, betaine and DMG, similar to those reported in the present analysis. The lack of significant associations may also be owing to the small sample size of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Our lack of association may also be attributed to the high plasma choline concentration (status) of the children in the Seychelles. A previous study only observed a relationship between plasma choline concentration and leucocyte ACh concentration in children who had low choline status (45) ; no relationship was evident in children who had plasma concentrations of choline, betaine and DMG, similar to those reported in the present analysis. The lack of significant associations may also be owing to the small sample size of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, Cho is an essential metabolite for the synthesis of acetylcholine in cholinergic neurotransmission. A previous study revealed a positive correlation between plasma Cho concentration and acetylcholine concentration in children with cystic fibrosis, and thus, the level of Cho could be used as an indicator of acetylcholine level in the brain. Acetylcholine is a neurotransmitter associated with attention, learning and memory, and Cho is important in cognitive processes and brain development .…”
Section: Discussionmentioning
confidence: 95%
“…Especially, Cho is an essential metabolite for the synthesis of acetylcholine (ACh) in cholinergic neurotransmission (Zeisel et al, 2006). According to Innis et al (2011), plasma Cho concentration is positively correlated with ACh concentration in children with cystic fibrosis. Thus, Cho indicates the level of Ach, which is a neurotransmitter involved in the functions of attention, learning, and memory.…”
Section: Discussionmentioning
confidence: 99%